Ukraine: Endemic Higher Education Corruption - Denisova-Schmidt, Elena; Prytula, Yaroslav (International Higher Education, 2017)
Based on a survey conducted among 600 students at selected public universities in Lviv, one of the largest Ukrainian cities, this contribution explores the determinants of several forms of student academic dishonesty and provides insights as to which groups of students are more likely to engage in either monetary or nonmonetary corruption.